ANALISIS KEBUTUHAN KOMPETENSI DAN PENYUSUNAN MODEL AWAL PELATIHAN IN-SERVICE BERBASIS KOMPETENSI DALAM MENINGKATKAN PROFESIONALISME BABY SITTER - Viena Rusmiati Hasanah (JIV-Jurnal Ilmiah Visi, 2017)
Baby sitters, at the present, though they are distributed through workers distribution services and have completed the training, all parties have not yet acknowledged their standards of competency. This research aims at analyzing the needs of competency and investigating competency-based in-service training model in order to improve baby sitters’ professionalism. This research utilizes qualitative research method with observation, interview and FGD (Forum Group Discuss) as the technique. The research was conducted at three of training institute for baby sitter in Bandung, West Java from January 2011 until August 2011. The results show that: 1) the analysis of competency’s needs shows that baby sitters at present need a training that can help them improve their ability and knowledge as well as competency based on the field’s needs and standards referring to standard imposed. 2) The conceptual model of competency-based in-service training comprises the development on mix standard competencies that are built, the determination of training management strategy, the strategy and learning method in the training, and various apparatus of training needed. The research concludes that baby sitters at present need improvement in their competencies in order to be professional in future.